Kontrollerad sönderbrytning vid skivrassprängning : inledande försök - Olsson, Mats; Nyberg, Ulf; Fjellborg, Stig (Luleå tekniska universitet, Institutionen för samhällsbyggnad och naturresurser, 2009)
This report describes some tests made in order to examine a number of important factors in sublevel caving. Among these factors were back-break, influence of a neighbour hole, rock movements in caving and the effect of compacted rock.The tests with back-break and influence of neighbour holes were performed in the abandoned open pit at Svappavaara, some 50 km south of Kiruna. The tests area was 100 m long with bench heights of 10-20 m. The area was divided into 4 test areas. Some 40 blast holes were drilled with a hole dimension of 115 mm and with a burden of 3 m. The 1st test area contained a sublevel drill layout of 8 holes but drilled downwards. The purpose here was to study the influence of a neighbour hole and back-break. The 2nd area consisted of a number of parallel vertical holes in two groups with different burdens. In the 3rd area three holes were drilled in a way to test the maximum spacing for breaking rock. The 4th area was again a test of the sublevel caving drill plan. The holes were charged with LKAB's standard emulsion KimuluxR 0500 for sublevel caving work.Measurements of the straightness of the holes were done. The detonation velocity was measured and the four rounds were high-speed filmed. The position of the bench front before and after blasting was measured with a stereo photogrammetric technique. The geology and the deviation of the holes were worse than expected and had an influence on the results. The maximum back-break occurred at tests with sublevel caving. It was possible to increase the burden to 3,5 m but with a coarser fragmentation. Furthermore fully charged 115 mm holes with a spacing of 7 m had no problem to break the burden. The velocity of the blasted front was measured to 13-21 m/s. Tests simulating sublevel caving were performed in the Kiruna mine by blasting a number of 64 mm and 115 mm holes drilled parallel with drift walls at different burdens. The walls were unconfined, i.e. free to move. A new method was invented consisting of an impact rod sliding in a measuring pipe. ...